Roughness receptivity in swept-wing boundary layers – experiments. (1st March 2010) - Carpenter, Andrew L.; Saric, William S.; Reed, Helen L.
The receptivity of boundary layer stability to micron-sized, spanwise-periodic discrete roughness elements (DREs) was studied. The DREs were applied to the leading edge of a 30-degree swept-wing. The test article was attached vertically to the port wing of a Cessna O-2A aircraft and operated at a chord Reynolds number of 6.5 to 7.5 million. Critically spaced DREs were applied at the leading edge to excite the crossflow instability and move transition forward. In this case, calibrated, multi-element hotfilm sensors were used to measure disturbance wall shear stress. The roughness height was varied from 0 to 50 microns both in the positive (bumps) and negative (dimples) sense. Thus, the disturbance amplitude variations were determined as a function of modulated DRE heights.